2017
DOI: 10.1021/acssuschemeng.6b03092
|View full text |Cite
|
Sign up to set email alerts
|

Well-Designed Hydrophobic Deep Eutectic Solvents As Green and Efficient Media for the Extraction of Artemisinin from Artemisia annua Leaves

Abstract: The green and efficient extraction of bioactive compounds from plant biomass is an important area of interest in the pharmaceutical industries. Hydrophilic deep eutectic solvents (DESs) have been considered as green alternatives to conventional solvents for bioactive compound extraction. In this study, we aimed to provide a practical example demonstrating the tunability of hydrophobic DESs as designer solvents to efficiently extract bioactive compounds from plant biomass. Artemisinin, known as the only drug ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(122 citation statements)
references
References 31 publications
4
118
0
Order By: Relevance
“…The PCE of the eutectic‐based cell was 2.5 %. These data well compare with our previous report on hydrophilic DES in DSSCs, thus confirming the suitability of HESs in DSSCs . The unconventional HES brings a number of advantages, such as the use of routine alkyl‐substituted record DSSC sensitizers, but without depressing the overall efficiency of the cell.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…The PCE of the eutectic‐based cell was 2.5 %. These data well compare with our previous report on hydrophilic DES in DSSCs, thus confirming the suitability of HESs in DSSCs . The unconventional HES brings a number of advantages, such as the use of routine alkyl‐substituted record DSSC sensitizers, but without depressing the overall efficiency of the cell.…”
Section: Figuresupporting
confidence: 90%
“…In parallel, Marrucho and co‐workers synthesized and characterized novel hydrophobic mixtures composed of dl ‐menthol and naturally occurring carboxylic acids, and tested (a) their extraction efficiencies towards biomolecules, and (b) for the extraction of pesticides from aqueous environment . A tailor‐made hydrophobic DES from methyl trioctyl ammonium chloride and 1‐butanol has also been recently set up by Su and co‐workers, and showed the highest extraction yield of bioactive Artemisinin from Artemisia annua leaves …”
Section: Figurementioning
confidence: 99%
“…The authors proposed a ternary hydrophobic (D)ES composed of methyl trioctylammonium chloride, capryl alcohol, and octylic acid at a molar ratio of 1:2:3 as the most efficient extractant. They also studied the extraction of artemisinin from artemisia annua leaves . Hydrophobic (D)ES based on methyltrioctylammonium chloride and 1‐butanol at a molar ratio of 1:4 showed the highest extraction yield and also a higher efficiency than the conventionally used organic solvent, petroleum ether.…”
Section: Hydrophobic (Deep) Eutectic Solventsmentioning
confidence: 99%
“…Comparison among DES-1, DES-2, and DES-3 indicated that the extraction yield with DES-1 was maximal. When the HBD/HBA molar ratio decreased from 2 : 1 to 1 : 2, the amounts of HBA increased, and thus resulted in the decrease in viscosity and surface tension, which would enhance their extraction efficiency [25,26].…”
Section: Comparison Of the Extractability Of Dessmentioning
confidence: 99%